IMPLEMENTASI MODEL PEMBELAJARAN KONTEKSTUAL BERBASIS AKHLAK KEMANDIRIAN - Rianawati, Rianawati (Analisis: Jurnal Studi Keislaman, 2014)
THEIMPLEMENTATIONOFMORALSANDINDEPENDENCE- BASED CONTEXTUAL LEARNING  MODELS  (Class Action Research  on Moral Subjects  in MAN 1 Pontianak):  This study explores  the  implementation  of  contextual  learning  in  order to improve student’s learning independence. The study was conducted in MAN I Pontianak using analytical models of Miles and Huerman.  The  study  concludes  that  : (1)  the  process  of learning  using  traditional   methods  tends  to  generate  negative output  marked with  : (a) students  are not accustomed  to think analytically,  (b) unable to give an opinion, (c) do not focus on learning, and (4) have a low absorption level; (2) On the contrary, through  contextual  learning methods,  students are able : (a) to design and to build their  knowledge,  (b) to conduct  a question and answer with a critical, systematic,  analytical  and logical; to be able to solve the  problem  together,  (c) to check the  results of learning, and to apply the knowledge gained.  (3) Contextual learning  model  proves  to  be  effective   in  improving  student learning independence.